IMAN DI ERA MEDIA DIGITAL:: KRITIK PAUS FRANSISKUS TERHADAP CULTURE OF INDIFFERENCE DALAM PERSPEKTIF TEOLOGI PUBLIK - Lawa, Felix (STT-RAI Batam, 2026)
This article aims to highlight Pope Francis’ critical view on the phenomenon of digitalization and the emergence of the culture of indifference, reading it within the framework of public theology. While previous studies have widely examined digital culture and papal teachings separately, there remains a gap in integrating Pope Francis’ social critique of digitalization within a coherent public theological perspective. This study argues that Christian faith does not merely operate in the private realm but also manifests in digital spaces as a prophetic and practical force that humanizes. The research is grounded in the reality that digital technological development presents a dual face: it opens vast opportunities for global communication, yet also fosters apathy, individualism, and the erosion of solidarity. Pope Francis considers this phenomenon not only a social issue but also a moral and theological crisis, as it undermines human dignity and weakens the bonds of love within society. Using a library research method with a qualitative-descriptive approach, this study offers a reinterpretative reading of Pope Francis’ thought within the horizon of public theology. The findings show that Pope Francis’ critique has four main characteristics: it is prophetic in unveiling social sins rooted in the culture of indifference; practical in proposing a culture of encounter as an alternative path; ecclesial in encouraging the Church’s active presence in digital spaces; and dialogical in opening engagement with technological developments to remain humane. This article contributes to the development of public theology by articulating a systematic synthesis between papal social teaching and digital culture, positioning digital space as a locus theologicus for contemporary Christian witness.